E-LKS OF POLYHEDRON MATERIAL BASED ON GUIDED DISCOVERY APPROACH TO FACILITATE MATHEMATICAL PROBLEM-SOLVING ABILITY OF JUNIOR HIGH SCHOOL - Ukhti Qodriyani; Susda Heleni (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2023)
This study aims to produce Electronic-based Student Worksheets (E-LKS) using a Guided Discovery approach on f polyhedron material based that are valid, practical, and potentially affect the Mathematical Problem-Solving Ability (KPMM) of junior high school. The research method used in this research is Research and Development using a 4-D development model consisting of four stages: Define, Design, Development, and Disseminate. Data collection techniques used include validation questionnaires, student response questionnaires, and documentation. This research involved students of class VIII MTs YASMI and IX MTs YASMI. The results showed that E-LKS has been valid from the quality of presentation, technical requirements, didactic requirements, construction requirements, and KPMM aspects with very valid criteria based on expert comments at the Expert Review and One-to-One stages. Next, the implementation of E-LKS at the Small Group and Field Test stage shows the practicality of E-LKS with very practical criteria. This can be seen from E-LKS, which is easy to read and use, and E-LKS can add enthusiasm to learning. The conclusion is that E-LKS uses a Guided Discovery approach to polyhedron material based to facilitate KPMM for junior high school students and has been valid and practically used in the learning process.